Injuries caused by aquatic animals in Brazil: an analysis of the data present in the information system for notifiable diseases - Reckziegel, Guilherme Carneiro (2015)
Introduction: We present a review of injuries in humans caused by aquatic animals in Brazil using the Information System for Notifiable Diseases [Sistema de Informacao de Agravos de Notificacao (SINAN)] database. Methods: A descriptive and retrospective epidemiological study was conducted from 2007 to 2013. Results: A total of 4,118 accidents were recorded. Of these accidents, 88.7% (3,651) were caused by venomous species, and 11.3% (467) were caused by poisonous, traumatic or unidentified aquatic animals. Most of the events were injuries by stingrays (69%) and jellyfish (13.1%). The North region was responsible for the majority of reports (66.2%), with a significant emphasis on accidents caused by freshwater stingrays (92.2% or 2,317 cases). In the South region, the region with the second highest number of records (15.7%), jellyfish caused the majority of accidents (83.7% or 452 cases). The Northeastern region, with 12.5% of the records, was notable because almost all accidents were caused by toadfish (95.6% or 174 cases). Conclusions: Although a comparison of different databases has not been performed, the data presented in this study, compared to local and regional surveys, raises the hypothesis of underreporting of accidents. As the SINAN is the official system for the notification of accidents by venomous animals in Brazil, it is imperative that its operation be reviewed and improved, given that effective measures to prevent accidents by venomous animals depend on a reliable database and the ability to accurately report the true conditions.